Ultrasonic cavitation finishing of 316 L stainless steel using different abrasive particles: A combined SPH simulation and experimental study - Jingsi, Wang; Liew, Pay Jun; Jiayuan, Wang; Qihang, Cui (Elsevier Ltd., 2025)
Ultrasonic cavitation and its driving effect on abrasive particles have been studied and applied to the surface finishing of 316 L stainless steel. To explore the influence of abrasive characteristic parameters on the surface finishing process, a cavitation-driven single abrasive impact model was established by coupling the smoothed particle hydrodynamics (SPH) method with the finite element method (FEM). The changes in the workpiece surface and the wear of abrasive particles after the impact were analysed, the effects of the abrasive particle size, material and shape were discussed, and the effectiveness of the model was verified through ultrasonic finishing experiments. SiC abrasive particles possessing irregular shape and Al2O3 abrasive particles possessing irregular and spherical shapes were used for comparison. Both simulation and experimental results indicate that the abrasive particle with a high hardness and a spherical shape has better material removal capability. However, the spherical abrasive particles tended to occur large cracks and split into small pieces, which accelerated the wear of the abrasives. In this work, the best finishing result was obtained by using irregularly shaped SiC abrasive particles, and the surface roughness Ra was improved by 12.87 %. This study provides a comprehensive understanding of the material removal process using cavitation-driven abrasives and examines the influence of key characteristics of abrasive particles. These insights are significant for advancing the application and enhancement of this technology in metal surface treatment.